For you - KRU; EMI (Malaysia). (Selangor : EMI (Malaysia), 1998)
Contains four different versions of the single taken from the album The Way We Jam.
For You / (3:49) -- For You blow your mind remix / (4:05) -- For You so right remix / (4:45) -- For You instrumental / (3:49)
Koleksi Khas Wiramanja.
Title from container.
Keywords: Songs, English -- Malaysia